A hierarchical customer satisfaction framework for evaluating rail transit systems of Istanbul - Aydin, Nezir; Celik, Erkan; Gumus, Alev Taskin (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
This paper provides a hierarchical customer satisfaction framework to measure rail transit lines' performances in Istanbul. The problems related to rail transit line systems are addressed via customer satisfaction surveys. Then, a framework is proposed combining statistical analysis, fuzzy analytic hierarchy process, trapezoidal fuzzy sets and Choquet integral to evaluate customer satisfaction levels. Next, the criteria need to be improved are determined and specific recommendations to enhance the operation for specific lines are suggested. The proposed framework provides directions for the future investments and it also can be used at a more macroscopic level to determine the operational deficiencies. Furthermore, it can be generalized and applied to complex decision making problems that include uncertain and subjective data or vague information. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Customer satisfaction; Rail transit systems; Multi criteria decision making; Fuzzy sets; DECISION-MAKING APPROACH; EXTENT ANALYSIS METHOD; FUZZY MCDM METHOD; SERVICE QUALITY; PUBLIC TRANSPORT; MULTIPLE-CRITERIA; PERFORMANCE EVALUATION; CAR; METHODOLOGY; PASSENGERS; Business & Economics; Transportation